Human Pluripotent Stem Cells: A Relevant Model to Identify Pathways Governing Thermogenic Adipocyte Generation - Yao, Xi; Dani, Vincent; Dani, Christian (Frontiers in Endocrinology, 2020)
Brown and brown-like adipocytes (BAs) are promising cell targets to counteract obesity thanks to their potential to drain and oxidize circulating glucose and triglycerides. However, the scarcity of BAs in human adults is a major limitation for energy expenditure based therapies. Enhanced characterization of BA progenitor cells (BAPs) and identification of critical pathways regulating their generation and differentiation into mature BAs would be an effective way to increase the BA mass. The identification of molecular mechanisms involved in the generation of thermogenic adipocytes is progressing substantially in mice. Much less is known in humans, thus highlighting the need for an in vitro model of human adipocyte development. Pluripotent stem cells (PSCs), i.e. embryonic stem cells and induced pluripotent stem cells, help gain insight into the different phases in the development of multiple cell types. We will discuss the capacity of human PSCs to differentiate into BAs in this review. Several groups, including ours, have reported low spontaneous adipocyte generation from PSCs. However, factors governing the differentiation of induced pluripotent stem cell-derived BA progenitors cells were recently identified, and the TGF signaling pathway has a pivotal role. The development of new relevant methods, such as the differentiation of hPSC-BAPs into 3D adipospheres to better mimick the lobular structure of human adipose tissue, will also be discussed. Differentiation of human PSCs into thermogenic adipocytes at high frequency provides an opportunity to characterize new targets for anti-obesity therapy.